The Impact of Job Performance Evaluations on Career Advancement Prospects: An Examination of Gender Differences in the IS Workplace - Igbaria, Magid; Baroudi, Jack J. (MIS Quarterly, 1995)
Despite the significant demographic changes in the work force projected by the year 2000 and beyond, little empirical research has been made on the obstacles faced by women in the field of computing. Since career advancement prospects are especially salient for IS employees, and IS workers are considered a distinct occupational group, it is important to understand the career advancement prospects of IS employees. This study examines the impact of gender on job performance evaluations, job performance attributions, and career advancement prospects. The results show that there are no significant gender differences in job performance ratings; however, women are perceived to have less favorable chances for promotion than men. We found that job performance ratings play an important role in influencing an individual’s chances for advancement. We also found that the effect of job performance on attributions is stronger among males than females. Additionally, we found that while the effect of job performance ratings on career advancement prospects is stronger among males, the effect of attributions on career advancement prospects is stronger among females. Suggestions regarding areas for future research are offered, and implications for human resource management are identified.